Orta kademe yönetiminin stratejik rolleri ile örgütsel performans ilişkisi ve stratejik rollere ilişkin uygulama örnekleri - Bakoğlu, Refika (My University, 1999)
Günümüz koşullarında emir-kumanda veya yukardan aşağıya strateji oluşturma modeline dayalı eski işbölümü anlayışı yavaş yavaş geçerliliğini yitirmeye başlamıştır. Strateji formülasyonu ve uygulanması terimi yerine daha bütünlükçü olan stratejinin biçimlendirilmesi terimi benimsenmeye başlanmıştır. Bunun anlamı stratejinin herhangi bir birey ya da bireylerin kafasında gelişmediğinin, aksine zaman içinde başarılı kararların ve aksiyonların etkileşimi yoluyla zamanla oluştuğunun kabul edilmesidir. Orta kademe yönetiminin üst ve alt kademe arasındaki ve soyut- somut bilgi arasındaki merkezi özgün pozisyonu, strateji sürecinde çok hayati bir konuma sahip olmalarına yol açmaktadır. Bu onların örgütün neler yapabileceği, hangi yeteneğinin geliştirilmesinin gerekli olduğu, mevcut yeteneklerinden nasıl rekabet avantajı sağlayabileceği, işlerin yapılışının yeni yolunun ne olabileceği ve firmanın değişim kapasitesinin nasıl genişletilebileceği konusunda özel bir yorum ve anlama şansına sahip olmaları olanağını beraberinde getirmektedir. Araştırmalar orta kademe yöneticilerinin stratejiye katılmalarının örgütsel performansı olumlu yönde etkilediğini ve özellikle yüksek performanslı firmaların orta kademe yöneticilerini stratejinin geliştirilmesi sürecine düzenli olarak kattıklarını ortaya çıkarmıştır. Araştırmalar hem stratejinin geliştirilmesi hem de uygulanması sürecinde orta kademe yönetiminin katılımının örgütsel performansı olumlu etkilediğini, ancak geleneksel görüşün aksine, yüksek örgütsel performansın stratejinin oluşturulması aşamasında orta kademe yönetiminin katılımıyla çok yakın ilişkili olduğunu göstermiştir. Yüksek performansı örgütler gözlenerek, stratejiye katkıya ve firmanın dinamik kapasitesini arttırmaya yönelik orta kademe yönetimine has dört stratejik rolün bulunduğu ortaya çıkarılmıştır. Etkinin yönü (yukardan aşağıya- aşağıdan yukarıya) ve bunun mevcut stratejiye etkisi ve stratejiye katkının doğası (faklılaştırıcı- bütünleştirici) arasındaki etkileşim bu dört stratejik rolün tanımlanmasını sağlamıştır. Bu rollerden stratejik alternatiflerin öncülüğü ve bilginin sentezlenmesi üst kademelere doğru stratejik etki, adaptasyonun kolaylaştırılması ve tasarlanan stratejinin uygulanması ise alt kademelere doğru stratejik etki faaliyetlerine dayalı olarak oluşmaktadır. Araştırmalar bu dört stratejik rol ile örgütsel performans arasında olumlu bir ilişkinin varlığını ortaya çıkarmıştır. Yüksek performans ile farklı düzeylerdeki üst kademelere doğru stratejik etki ve benzer düzeylerdeki alt kademelere doru stratejik etki arasında olumlu ilişkinin varlığı tespit edilmiştir. Araştırmalar stratejilerinde ürün yeniliğini ön plana koyan, yeni Pazar olanağı araştıran ve örgütsel öncelikleri esnek bırakan firmaların orta kademe yöneticilerinin dar ürün yelpazesine ve düşük örgütsel etkinliğe sahip firmalarınkinden çok daha yüksek öncülük ve kolaylaştırma rolüne sahip olduklarını ortaya koymuştur. Araştırmalar ayrıca bazı orta kademe yöneticilerinin, özellikle alan belirleyici olanların, daha yüksek düzeyde öncülük rolünü gerçekleştirdiklerini göstermiştir. Orta kademe yöneticilerinin herhangi bir stratejik role yeteneği ve istemesi yöneticiden yöneticiye değişmektedir. Yeni sistemler ve yapıların oluşturulmasındaki faydaları ve konumlandırılmaları da bunu etkilemektedir. Ayrıca orta kademe yönetiminin alan belirleyiciliği birimindeki biçimsel pozisyonu da bu roller açısından önemli bir faktör olarak görünmektedir. Temel yetenekleri başarılı bir şekilde geliştiren firmalarda orta kademe yönetiminin farklı stratejik davranışlara sahip olması beklenmelidir. Araştırmalar stratejik rollerin performansındaki çeşitlilik ile ekonomik performansın ilişkili olduğunu ortaya çıkarmıştır. Bu orta kademe yönetiminin rekabet avantajı elde edilmesine yönelik örgütsel yeteneklerin oluşturulması sürecinde hayati öneminin bulunduğuna dair ilk kanıt olarak değerlendirilebilir. Daha tutarlı alt kademelere doğru stratejik etki ile daha farklılaşmış üst kademelere doğru etki, örgütsel performansı olumlu yönde etkilemektedir. Kısaca orta kademe yönetiminin hem stratejinin tanımlanmasında hem de uygulanmasında sürece katılması anlamlıdır. Orta kademe yönetiminin stratejiye katılması stratejik karar verme sürecinin önemli bir unsurudur. Her orta kademe yöneticisi stratejiyi eşit düzeyde etkilememeli ve orta kademe yöneticileri stratejik etkilerinin zaman içinde farklılaşmasını kabul etmelidirler.

It is accepted that the command-and-control (top-down) model of strategy and the old division of work no longer applies in today's environment. Instead of using the terms formulation and implementation a more holistic term, formation has been adopted to describe the strategic division of work. This means that instead of strategies developing from the minds of top managers or individuals, they develop over time through successive interaction of decisions and actions, as all the evidence suggests. Thus all the members of any organisation have to think and act more strategically. Due to their centrality and unique position between the top and the operating level and their knowledge, middle managers are the key actors in the strategic process. They are linking actors between the firm and its environment and between strategic and operational decision making. It is accepted that this linking function is crucial in deploying and gaining advantage from existing capabilities, in accumulating methods and broadening their firms' capability to change. The findings suggest that the involvement of middle managers in strategy affects organisational performance and in high-performing firms middle managers are regularly involved in the development of organisational strategy. Middle managers especially impact and improve on organisational performance when involved in the formulation of strategy. Middle managers have four strategic roles in high performing organisations which contribute to strategy and advance the firm's dynamic capability. The interaction of direction of influence - upward and downward - and its impact on existing strategy - divergent and integrative - leads to a description of four strategic middle management's roles. The roles are defined as follows: championing strategic alternatives; synthesizing information; facilitating adaptability and implementing deliberate strategy. Championing strategic alternatives basically means bringing entrepreneurial and innovative proposals to the attention of the top management and is the upward form of strategic influence. İt has a divergent nature in its contribution to strategy. Synthesizing information also comes from upward influence but it has an integrative contribution to strategy. The middle management's position between strategy and operations provides a unique perspective for integrating diverse information coming from both inside and outside the organisation. Thus, in addition to championing strategic proposals, middle managers frequently supply information to top management. Events are reported as threats or opportunities and these labels are a powerful influence on how superiors or top management see their situation. This means that middle managers are often able to control or at least influence top management perceptions by framing information in certain ways. This process, however, is not necessarily conscious or manipulative. This role can be crucial in encouraging cautious top managers to take needed risks. Facilitating adaptability is the downward form of strategic influence and its contributive nature to strategy is divergent. Middle managers make their organisations more flexible and stimulate behaviour that can diverge from official expectation. There is a tendency for them to be change masters when they encourage cross-functional problem solving, experimentation, and learning rather than being change resisters. Middle management's most commonly recognized strategic role is implementation of deliberate strategy or the top management's intention. In this role, the strategic contribution rests on the middle manager's efforts to deploy existing resources efficiently and effectively. In championing, synthesizing, and facilitating, middle managers go beyond or sometimes even ignore the plans embedded in the top management's deliberate strategy. Implementing deliberate strategy involves intervening in the organisation's existing operations as well as creating new systems and structures. In short, that means it helps to redeploy organisational capabilities. Findings suggest that in organisations whose strategy depended on product innovation, exploiting new market opportunities, and maintaining flexible organisational priorities have significantly higher levels of middle management championing and facilitating, when compared to organisations whose strategy relied on narrow product lines and organisational efficiency. Findings also suggest that certain middle managers, who are boundary spanners, tend to be greater champions than others. In particular, managers in marketing, sales, purchasing, and R&D who are engaged in significantly more championing behaviour than managers from other functions. Middle managers are likely to differ widely in their ability and willingness to assume a strategic role at a particular point in time. Middle managers' formal position within a boundary-spanning subunit appears as another significant factor. More importantly, the relevance and usefulness of particular managers depends on the strategic situation. In firms that successfully develop core capability, considerable variation in the types of middle management strategic behavior should be expected. The findings also suggest that variation in the performance of the strategic roles is highly associated with the economic performance of the firms in the research. This is considered as major evidence supporting the proposition that middle managers are provital in the creation of the organisational capabilities that form the basis of competitive advantage. More consistency of downward influence and more varied upward influence are positively associated with measures of organisational performance. In short, middle management involvement is significant in both the definition and execution of strategy and it is their inclusiveness which is vital in bringing the strategic decision process into formation. However, not all middle managers should influence strategy equally, and managers should expect their own influence to vary over time.
Keywords: STRATEJİK YÖNETİM-Şirketler; YÖNETİM_Şirketler